Health promotion practice : power and empowerment - Laverack, Glenn (SAGE, 2009)
Health Promotion Practice explores the issue of how such an approach to health promotion practice can improve a community's success towards achieving healthier conditions through its own actions. Placing empowerment at the heart of health promotion practice, and offering advice for health promoters who accept the challenge to work in such a way, Health Promotion Practice defines key concepts of health, health promotion and community empowerment.